2019
DOI: 10.1097/scs.0000000000005667
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Computed Tomography Scan for Orbital Fracture Reconstruction

Abstract: Orbital fractures pose specific challenge in its surgical management. One of the greatest challenges is to obtain satisfactory reconstruction by correct positioning of orbital implant. Intraoperative computed tomography (CT) scan may facilitate this procedure. The aim of this study was to describe the early use of intraoperative CT in orbital fractures repair in our center. The authors assessed the revision types and rates that have occurred with this technique. With the use of pre-surgical planning, optical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
2
18
0
3
Order By: Relevance
“…O-arm intraoperative CT as one of computer-assisted components in OBFs reconstruction has led to a positive change in operative management, even in our small series, as described above. This further emphasises the usefulness of this surgical tool in optimising orbital fracture repair and is in accordance with previous studies (Borad et al, 2017;Cannizzaro et al, 2017;van Hout et al, 2014, Nazimi et al, 2019a. From two-dimensional to three-dimensional images, the use of image fusion techniques could further enhance the potential of intraoperative CT imaging and has more to offer for primary delayed or for secondary OBFs reconstruction (Zizelmann et al, 2007;Heiland et al, 2004;2005).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…O-arm intraoperative CT as one of computer-assisted components in OBFs reconstruction has led to a positive change in operative management, even in our small series, as described above. This further emphasises the usefulness of this surgical tool in optimising orbital fracture repair and is in accordance with previous studies (Borad et al, 2017;Cannizzaro et al, 2017;van Hout et al, 2014, Nazimi et al, 2019a. From two-dimensional to three-dimensional images, the use of image fusion techniques could further enhance the potential of intraoperative CT imaging and has more to offer for primary delayed or for secondary OBFs reconstruction (Zizelmann et al, 2007;Heiland et al, 2004;2005).…”
Section: Discussionsupporting
confidence: 87%
“…Currently, it may also not be readily available for many institutions, with costs and/or the amount of radiation exposure as primary concerns. In recent publications, intraoperative CT has been regarded as an essential tool for the facial reconstructive surgeon in optimising surgical repair (Borad et al, 2017;Nazimi et al, 2019a). The use of intraoperative CT with O-arm also suggested that the imaging led to a significant change in operative management (Borad et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We attribute this to the use of intraoperative CT, which allows for precise anatomic positioning of the implant. As shown by Nazimi et al 21 the use of intraoperative CT allows for real-time assessment of fracture reduction and immediate implant orbital revision, circumventing the need for postoperative imaging. To the authors’ knowledge there have been no studies reported on the outcomes of the 3D titan implant and use of intraoperative CT for two-wall orbital reconstruction.…”
Section: Discussionmentioning
confidence: 99%